The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1108/tqm-06-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

An ANP based selective assembly approach incorporating Taguchi’s quality loss function to improve quality of placements in technical institutions

Abstract: Purpose – The performance of technical institutions in India is reflected through the level of campus placements. It is vital for them to have efficient, effective and robust placement policies. Selective assembly is a technique used in manufacturing industry in improving the quality of assemblies from relatively low-quality components. The purpose of this paper is to develop a methodology using selective assembly approach to improve the quality of placements of technical institutions in India.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, in most cases, the top performers contemplate on leaving while the low/mediocre performers remain with the organization. Examining the predictors of turnover intention is critical for the managers, as consequences of turnover lead to reduced profits, due to increased employment cost and poor performance (Upadhayay and Vrat, 2016). Skelton et al (2019) have stated that identifying the determinants of employee turnover in manufacturing companies is crucial from both business and social perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in most cases, the top performers contemplate on leaving while the low/mediocre performers remain with the organization. Examining the predictors of turnover intention is critical for the managers, as consequences of turnover lead to reduced profits, due to increased employment cost and poor performance (Upadhayay and Vrat, 2016). Skelton et al (2019) have stated that identifying the determinants of employee turnover in manufacturing companies is crucial from both business and social perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Hancock et al (2013) suggested a significant correlation exists between the financial performance of manufacturers and employee turnover, which makes turnover intent an important area of study for the manufacturing industry. Upadhayay and Vrat (2016) noted total employee turnover expenses could cost businesses more than 100 per cent of a single employee's annual wages or salary, depending on the job left unoccupied. These scholars noted employee turnover decreases profits due to increased hiring costs and weaker (Upadhayay and Vrat, 2016).…”
Section: Inferential Statisticsmentioning
confidence: 99%
“…Upadhayay and Vrat (2016) noted total employee turnover expenses could cost businesses more than 100 per cent of a single employee's annual wages or salary, depending on the job left unoccupied. These scholars noted employee turnover decreases profits due to increased hiring costs and weaker (Upadhayay and Vrat, 2016). Therefore, understanding the variables that might contribute to turnover intent remains important.…”
Section: Inferential Statisticsmentioning
confidence: 99%
“…Addressing the factors that cause turnover is vital to retain potential and talented employees as well as to reduce excess expenditure associated with turnover. Upadhayay and Vrat (2016) noted that turnover expenses might cost businesses with more than 100% of a single employee's annual wages or salary. Turnover also discourages other employee's morale leading to work instability and disruptions (Pertiwi, 2018).…”
Section: Introductionmentioning
confidence: 99%